TINJAUAN HUKUM ISLAM TERHADAP SISTEM KEMITRAAN BAGI HASIL DARI LAHAN PLASMA SAWIT - Habibie, Ramadhani Alfin (Fakultas Syariah, 2019)
The profit sharing agreement is a binding contract. Plasma Land as the agreement object involves three parties, they are PT. Bumitama Gunajaya Abadi as the manager Mitra Behaum Cooperative as the bridge between community and company distributing oil palm monthly, and society as the owners of plasma land provided by local government. The grant of plasma land from local government that has no assurance becomes this study object. Types of profit sharing agreement for agricultural or farm products in Islamic law are: musaqah, muzara’ah and mukhabarah. The study discusses whether the profit sharing of oil palm includes in either one of the systems or creates new case in farm’s profit sharing. The researcher believes that further research should be done answering this problem. The result shows that the agreement used tends to be mukhabarah, that is a cooperation between land manager and owner in agriculture or farm. However, we cannot say the agreement is appropriate for some aspects. In its practice, it imperfect is that there is no exact location or assurance of the land. Next, in term of sharing profit, they already set clear share in percentage which is in line (not gharar) with the requirements of mukhabarah.Akad bagi hasil merupakan akad kerjasama yang bersifat mengikat. Lahan Plasma sebagai objek dari akad melibatkan tiga pihak didalamnya yaitu PT. Bumitama Gunajaya Abadi (BGA), Koperasi Mitra Behaum, serta masyarakat selaku pemilik lahan plasma yang diberikan oleh Pemerintah Daerah (Pemda). Pemberian lahan plasma dari pemda yang tidak memiliki kepastian letak inilah yang menjadi objek penelitian. Akad kerjasama bagi hasil pertanian atau perkebunan dalam hukum Islam adalah dalam bentuk musaqah, muzara’ah dan mukhabarah. Persoalan yang muncul adalah apakah bagi hasil dalam perkebunan sawit tersebut termasuk dari salah satu dari sistem bagi hasil tersebut ataukah menimbulkan persoalan baru dalam bagi hasil perkebunan. Hasil penelitian adalah kerjasama perkebunan sawit dapat dimasukkan dalam akad mukhabarah yaitu bentuk kerjasama antara pengelola kebun dan pemilik lahan. Beberapa rukun dan syarat sebagian telah terpenuhi, namun ada salah satu syarat yang belum terpenuhi yaitu pada tanah yang akan ditanami tidak memiliki kepastian letak. Ketidakpastian ini yang menyebabkan kurang sempurnanya syarat mukhabarah.